YNTKTS' hingga 'GWS': Transformasi Akronim sebagai Strategi Komunikasi Generasi Digital - Faiz, Moh (Maliki Interdisciplinary Journal, 2025)
This article examines the phenomenon of acronym transformation in digital communication as a form of linguistic efficiency and identity expression of the younger generation in the era of social media. Through conceptual and historical analysis approaches, this research reveals how abbreviations such as YNTKTS and GWS represent the adaptation of language structures to the demands of fast, concise, and creative communication. Platforms such as TikTok, Twitter, and Instagram are positioned as linguistic laboratories where language evolution occurs at high speed, giving rise to new communication systems that are efficient and inclusive. The findings show that digital acronyms are not just character-saving tools, but also symbols of resistance to conventional language norms and tools for negotiating the identities of generations Z and Alpha. The article also highlights the tension between prescriptivism and descriptivism in linguistics, and its implications for education, public communication and national language policy. The research recommends a more adaptive and participatory approach to linguistics, in order to create an Indonesian language ecosystem that is dynamic, relevant, and remains rooted in national identity.